2010
DOI: 10.1128/aac.00529-10
|View full text |Cite|
|
Sign up to set email alerts
|

Mutually Exclusive Genotypes for Pyrazinamide and 5-Chloropyrazinamide Resistance Reveal a Potential Resistance-Proofing Strategy

Abstract: The pyrazinamide (PZA) analog 5-chloropyrazinamide (5-Cl PZA) is active against mycobacterial species, including PZA-resistant strains of Mycobacterium tuberculosis. In M. smegmatis, overexpression of the type 1 fatty acid synthase (FAS I) confers resistance to 5-Cl PZA, a potent FAS I inhibitor. Since M. tuberculosis and M. bovis cannot tolerate FAS I overexpression, 5-Cl PZA resistance mutations have yet to be described for tubercle bacilli. In an attempt to identify other factors that govern the activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
(50 reference statements)
1
15
0
Order By: Relevance
“…Once in the cytoplasm, the proton dissociates from POA, and the cycle continues until the cytoplasmic pH equilibrates with that of the extracellular environment. Inconsistent with this model, the acid dependence of PZA activity can be abolished by incubation under alkaline pH (5), by overexpression of pncA (19), or by preventing POA from cycling in and out of the cell by the addition of efflux pump inhibitors (4). Moreover, it has been demonstrated that the primary in vivo niches for M. tuberculosis, phagocyte lysosomes and tubercular granulomas, do not acidify when live bacilli are present (20,21).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Once in the cytoplasm, the proton dissociates from POA, and the cycle continues until the cytoplasmic pH equilibrates with that of the extracellular environment. Inconsistent with this model, the acid dependence of PZA activity can be abolished by incubation under alkaline pH (5), by overexpression of pncA (19), or by preventing POA from cycling in and out of the cell by the addition of efflux pump inhibitors (4). Moreover, it has been demonstrated that the primary in vivo niches for M. tuberculosis, phagocyte lysosomes and tubercular granulomas, do not acidify when live bacilli are present (20,21).…”
mentioning
confidence: 97%
“…The first of these models comes from studies involving the PZA structural analog 5-chloropyrazinamide (5-Cl PZA), which was found to be a potent inhibitor of the mycobacterial fatty acid synthase I (FAS-I) (16)(17)(18). While M. tuberculosis FAS-I activity was found to also be compromised by PZA treatment (16,18,19), in situ evidence for this inhibition has been confounded by the inability to overexpress FAS-I in M. tuberculosis (16). The model has also been challenged by a report in which inhibition of purified FAS-I by POA was not observed, and FAS-I inhibition in whole cells was suggested to be a downstream consequence of POA-mediated organic acid stress (17).…”
mentioning
confidence: 99%
“…On the basis of these and other findings, a number of models have been proposed to explain the antimycobacterial action of PZA and POA, including direct inhibition of fatty acid synthase I (10), disruption of the membrane potential and cytoplasmic pH homeostasis via a protonophore activity (11), inhibition of transtranslation (12), and inhibition of the aspartate decarboxylase PanD, involved in pantothenate and coenzyme A (CoA) biosynthesis (13). While the bases for these models provide clues toward understanding PZA and POA susceptibility, fundamental aspects of these models have been challenged by recent reports (7,(14)(15)(16)(17)(18)(19). Consistent with a role for PanD in PZA action, it has recently been demonstrated that exogenously supplied intermediates of the CoA biosynthetic pathway can antagonize PZA activity, point mutations in panD are associated with in vitro PZA resistance, and PZA treatment leads to the depletion of intrabacterial levels of pantothenate and CoA (13,15,20).…”
mentioning
confidence: 99%
“…Recent reports have revealed that the acid dependence of PZA action can be diminished through coincubation with efflux pump inhibitors (18,27) or by overexpression of PncA (28). Nonetheless, proton shuttling resulting in cytoplasmic acidification remains a plausible but untested model for PZA action.…”
mentioning
confidence: 99%